Process chemistry of coal utilization : impacts of coal quality and operating conditions - Niksa, Stephen (Woodhead Publishing in energy., 2020)
Process Chemistry of Coal Utilization: Reaction Mechanisms for Coal Decomposition and Volatiles Conversion relates major advances in coal science on how to interpret performance data from lab, pilot and commercial scales. The book presents a very broad range of quantitative methods, from statistical regressions, to rudimentary models, CFD and comprehensive reaction mechanisms. Combining the latest research in the field, including an abundance of lab datasets, the book illustrates how a particular operating condition affects a specific coal-based reaction system. Managers who use these tactics will be able to tailor their testing and simulation work to effectively characterize and solve their problems. --